The Impact of Teacher Welfare on School Effectiveness - Listiani, Feby Eka; Darmawan, Diki; Maharani, Nadhifa Ardhiana; Aprilia, Rengga; Qodariswati, Tri Lailatul; Windasari, Windasari (History Education, University of Jember, 2024)
Educational institutions have a crucial role in improving the quality of human resources, creating educated personnel who are able to face very rapid changes. The aim of this research is to find out and analyze an in-depth analysis of teacher welfare and school effectiveness at 5 schools: SDI Kyai Ibrahim Surabaya, SDN Kutisari 1, SDN Keboananom, SDN Siwalankerto 1, SDN Kutisari 2. This research uses quantitative methods and the research subject is School educators or teachers. The data collection technique employed in the quantitative method involves the use of linear regression XY, with X representing teacher well-being and Y representing school effectiveness. Data are gathered through Google Forms, and journal analysis serves as a reference and theoretical foundation. The research activities commence with identifying the research topic, followed by determining the title, collecting field data, and concluding with the creation of findings and a report. The results of this study indicate that variable X teacher welfare does not have a significant effect on variable Y school effectiveness. This can be shown from the regression analysis test results which show that the sig value is more than 0.05, with a sig value of 0.103. So that H0 is accepted and H) is not accepted.